Passional Atheism, Passional Agnosticism and ‘The Will to Believe’ - Molto, Daniel (Religions, 2025)
Jack Warman and Joshua Cockayne have recently claimed that the arguments that William James provides in his famous lecture ‘The Will to Believe’ to justify passional theism would equally justify passional atheism. They are correct in this claim, but there is in fact more than one way that a non-theistic doxastic attitude can be passionally justified given what is said in James’s lecture. In addition to outright, passionally motivated, atheistic belief, there is also the possibility of arriving at theistic non-belief (henceforth ‘agnosticism’) when the passional reasons for adopting theism (even where that option is “live”) are overcome by the passional reasons for not adopting theism. James takes great pains to argue against the claim that we must prefer passional non-belief over passional belief, but he does not argue that we must prefer passional belief over passional non-belief and, in fact, he explicitly denies this, or so I shall argue. Thus, on my interpretation of the lecture, the choice to go without religious belief, even where that option is presented as forced, momentous and live, can be passionally justified. Moreover, so can the adoption of outright atheistic belief for passional reasons.